Native language interference toward second language Diphthong production among TESL students / Muhammad Izdihar Rijap - Rijap, Muhammad Izdihar (Faculty of Education, 2014)
The study was conducted to investigate whether the native language has a direct interference toward the pronunciation of diphthong in the second language or not. The population of the study were of TESL students of Universiti Teknologi MARA. The sampling technique used is the purposive sampling and 6 students of the Faculty of Education were chosen. Interviews were used as the research instruments of the study. The researcher personally interviewed each participant. The Contrastive Analysis Hypothesis was used to analyse the data collected. This research revealed that all participants experienced language transfer toward their second language diphthong pronunciation. This paper also considered the implications of all findings in improving the quality of TESL students as well as the curriculum provided for them.